2011
DOI: 10.4238/2011.november.10.4
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum triggers broad changes in microRNA expression in rice roots

Abstract: ABSTRACT. MicroRNAs are small 21-nucleotide RNA molecules with regulatory roles in development and in response to stress. Expression of some plant miRNAs has been specifically associated with responses to abiotic stresses caused by cold, light, iron, and copper ions. In acid soils, aluminum solubility increases, thereby causing severe damage to plants. Although physiological aspects of aluminum toxicity in plants have been well characterized, the molecular mediators are not fully elucidated. There have been no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…To overcome such toxicity, plants have evolved various strategies to adapt to environmental stresses. Previous research revealed that the regulatory mechanisms of plants in response to stresses are complex, and many miRNA genes function in the processes of stress 65,66 whereas >60 miRNAs were found to be involved in the process of arsenite response in this study (see the Supporting Information). Seven family members including miR1318, miR1861, miR2121, miR810, miR812, miR815, and miR818 were significantly down-regulated after the treatment of arsenite.…”
Section: ■ Discussionmentioning
confidence: 81%
“…To overcome such toxicity, plants have evolved various strategies to adapt to environmental stresses. Previous research revealed that the regulatory mechanisms of plants in response to stresses are complex, and many miRNA genes function in the processes of stress 65,66 whereas >60 miRNAs were found to be involved in the process of arsenite response in this study (see the Supporting Information). Seven family members including miR1318, miR1861, miR2121, miR810, miR812, miR815, and miR818 were significantly down-regulated after the treatment of arsenite.…”
Section: ■ Discussionmentioning
confidence: 81%
“…MicroRNA was quantified according to Lima et al (2011). Total RNA was reverse transcribed using M-MLV Reverse Tramscriptase (Promega).…”
Section: Rna Extraction and Gene Expression Analysismentioning
confidence: 99%
“…The importance of F-box proteins to plant growth and development is further evidenced by the expression of several F-boxencoding genes under additional post-transcriptional regulation by a class of small regulatory nonprotein-coding RNAs, termed microRNAs (miRNAs). A number of molecular approaches have shown that the expression levels of F-box protein encoding genes, Transport Inhibitor Response 1 (TIR1), Leaf Curling Responsiveness (LCR) and More Axillary Growth 2 (MAX2) are regulated via miR393-, miR394-, and miR528-directed mRNA-cleavage, respectively (12)(13)(14).…”
mentioning
confidence: 99%